Acute COVID-19 and LongCOVID syndrome – molecular implications for therapeutic strategies - review - Krzysztof Piotr Michalak; Amelia Zofia Michalak; Alicja Brenk-Krakowska (Frontiers in Immunology)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has been recognized not only for its acute effects but also for its ability to cause LongCOVID Syndrome (LCS), a condition characterized by persistent symptoms affecting multiple organ systems. This review examines the molecular and immunological mechanisms underlying LCS, with a particular focus on autophagy inhibition, chronic inflammation, oxidative, nitrosative and calcium stress, viral persistence and autoimmunology. Potential pathophysiological mechanisms involved in LCS include (1) autoimmune activation, (2) latent viral persistence, where SARS-CoV-2 continues to influence host metabolism, (3) reactivation of latent pathogens such as Epstein-Barr virus (EBV) or cytomegalovirus (CMV), exacerbating immune and metabolic dysregulation, and (4) possible persistent metabolic and inflammatory dysregulation, where the body fails to restore post-infection homeostasis. The manipulation of cellular pathways by SARS-CoV-2 proteins is a critical aspect of the virus’ ability to evade immune clearance and establish long-term dysfunction. Viral proteins such as NSP13, ORF3a and ORF8 have been shown to disrupt autophagy, thereby impairing viral clearance and promoting immune evasion. In addition, mitochondrial dysfunction, dysregulated calcium signaling, oxidative stress, chronic HIF-1α activation and Nrf2 inhibition create a self-sustaining inflammatory feedback loop that contributes to tissue damage and persistent symptoms. Therefore understanding the molecular basis of LCS is critical for the development of effective therapeutic strategies. Targeting autophagy and Nrf2 activation, glycolysis inhibition, and restoration calcium homeostasis may provide novel strategies to mitigate the long-term consequences of SARS-CoV-2 infection. Future research should focus on personalized therapeutic interventions based on the dominant molecular perturbations in individual patients.